Surviving the Committee of Enquiry: A Thriving BBC (1922–1995) - Daniel Ruff (Revue Française de Civilisation Britannique)
The BBC has been subjected to legitimate public scrutiny throughout its history. Governments have regularly commissioned committees of enquiry to study its role, its values, its programmes, its funding, its future. Far from destabilising the Corporation, these enquiries have tended—sometimes against expectations—to confirm the importance of the BBC in the life of the nation. Although programmes and technologies have evolved beyond recognition since his time, Reith’s founding principles of public service broadcasting have been endorsed time and again. The BBC and its funding model are never completely out of the woods; but a longer view of the constant cycle of public enquiries shows that it is in every sense hard to beat.